Developing Coconut Milk Ice Cream Using Stabilizers from Okra Mucilage Powder - Chompuja, Sungwan; Thonabut, Janya; Uprarawanna, Utsaphong; Khunsee, At (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2023)
This research study aimed to select a suitable recipe for making coconut milk ice cream using okra mucilage powder as a stabilizer and determine the optimal amount of okra mucilage powder for the recipe. A completely randomized block (RCBD) experiment was planned for sensory analyses and a completely randomized experiment (CRD) was planned for physical, chemical and microbial analyses. The results showed that appropriate amount of okra mucilage powder was 5 grams (0.50 %), which received favorable sensory preference scores for color (7.90±1.21), taste (7.40±0.86), and overall preference (7.46±1.11) on a 9-Point Hedonic Scale. However, no significant differences were observed in scores for appearance and smell. By substituting okra mucilage powder for guar gum, the viscosity and overrun percentage of the ice cream mixture were reduced, resulting in an appropriate texture and slower melting. The physical, chemical, and biological analyses revealed L*, a*, and b* values of 45.68, 0.85, and 8.22, respectively, a pH value of 6.80, water-soluble solids content of 25.1 brix, overrun percentage of 21.83, and viscosity of 3,174 centipoise (cp). The chemical analysis showed moisture, fat, protein, fiber, and carbohydrate percentages of 71.04, 1.67, 4.83, 0.45, 1.57, and 20.44, respectively, with a total energy of 116.11 kilocalories per 100 grams. This study highlights the potential use of okra mucilage powder as a stabilizer in ice cream production, providing added value to okras and exploring new applications.